PEMBINAAN POLA HIDUP SEHAT “CERDIK” PADA LANSIA RISIKO DAN HIPERTENSI DI KELURAHAN PAJAJARAN KOTA BANDUNG - Supriadi Supriadi; Achmad Husni (Poltekkes Kemenkes Bandung, 2022)
Hypertension has killed 9.4 people worldwide every year. WHO estimates that the number of people with hypertension will continue to increase along with the growing population. In 2025, it is projected that around 29% of the world's population is affected by hypertension and currently the highest percentage is in developing countries. In Southeast Asia, 36% of adults suffer from hypertension. High blood pressure can be prevented by changing your lifestyle. The Ministry of Health seeks to increase self-awareness through the activities of the integrated non-communicable disease development post (Pos Bindu PTM). People are invited to behave smart, namely regular health checks, getting rid of cigarette smoke and other air pollution, diligent physical activity, healthy diet with balanced calories, adequate rest, and managing stress. The public can also know the risk factors, detection, treatment, and management of hypertension emergency response. In this regard, the Health Polytechnic of the Ministry of Health Bandung contributes to efforts to prevent and manage hypertension clients, so that their quality of life is better, namely through science and technology development programs for the community or community service as one of the three dharmas of higher education. After fostering a